2021
DOI: 10.1002/lary.29716
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic Disparities in Pediatric Cochlear Implantation Access and Use: A Systematic Review

Abstract: Objectives: Pediatric cochlear implantation (CI) is a multistep process, which exposes a healthcare system's potential weaknesses in ability to deliver timely care to deaf children. The current systematic review aims to determine the sociodemographic disparities that predict pediatric CI access and use among CI candidates and recipients across the world. We hypothesize that sociodemographic factors independently influence CI access and use within a given country.Study Design: Systematic review. Methods: A qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 49 publications
2
3
0
Order By: Relevance
“…Black children are less likely to receive tonsillectomy or cochlear implants, and more likely to have complications following such surgeries. 7,29,30 Our results indicate that this finding is potentially also true of surgical management of RPA. Because Black children were more likely to be antibiotic naïve upon presentation to the hospital, a possible explanation is that a trial of medical therapy was favored prior to attempting surgical management.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Black children are less likely to receive tonsillectomy or cochlear implants, and more likely to have complications following such surgeries. 7,29,30 Our results indicate that this finding is potentially also true of surgical management of RPA. Because Black children were more likely to be antibiotic naïve upon presentation to the hospital, a possible explanation is that a trial of medical therapy was favored prior to attempting surgical management.…”
Section: Discussionsupporting
confidence: 64%
“…The finding that Black patients are less likely to receive surgical management of otolaryngologic disease has been demonstrated across numerous subspecialties of pediatric otolaryngology. Black children are less likely to receive tonsillectomy or cochlear implants, and more likely to have complications following such surgeries 7,29,30 . Our results indicate that this finding is potentially also true of surgical management of RPA.…”
Section: Discussionsupporting
confidence: 51%
“…Although national trends in clinical practice typically lag behind guideline updates, the plateaued age at implantation over recent years may implicate several factors other than FDA labeling and practice guidelines that have impeded implantation in younger children. Delayed implantation in the pediatric population may result from patient or systemic factors including socioeconomic barriers, lack of access to care, issues surrounding insurance coverage and poor reimbursement, and obstacles associated with cumbersome hearing health care pathways (35)(36)(37)(38)(39)(40). In 2019, the Centers for Disease Control and Prevention estimated that over 98% of newborns were screened for hearing loss, and that almost 6,000 U.S. infants were identified with some level of permanent hearing loss (41).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple previous studies have concluded that socioeconomic status-particularly race/ethnicity, insurance, and income-may have a significant impact on access to implantation, which is manifested either in the overall number of implantations or the likelihood of early implantation among these populations (9). Using the HCUP Kids' Inpatient Database, both Tampio et al (10) and Stern et al (12) found that incidence rates of pediatric implantations were decreased in Hispanic and Black children, although the former did note that rates among Hispanic children increased from 1997 to 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Alongside these data showing benefit for early implantation, demand for pediatric cochlear implantation has also continued to grow. However, disparities in rates of cochlear implantation have persisted (9). Black and Hispanic children are less likely to undergo implantation than White and Asian children (10), and lower household income has been associated with later age at implantation (11).…”
Section: Introductionmentioning
confidence: 99%